The significance of peroxisome function in chronological aging of Saccharomyces cerevisiae. Issue 5 (8th July 2013) - Lefevre, Sophie D.; van Roermund, Carlo W.; Wanders, Ronald J. A.; Veenhuis, Marten; van der Klei, Ida J.
Summary: We studied the chronological lifespan of glucose‐grown Saccharomyces cerevisiae in relation to the function of intact peroxisomes. We analyzed four different peroxisome‐deficient ( pex ) phenotypes. These included Δ pex3 cells that lack peroxisomal membranes and in which all peroxisomal proteins are mislocalized together with Δ pex6 in which all matrix proteins are mislocalized to the cytosol, whereas membrane proteins are still correctly sorted to peroxisomal ghosts. In addition, we analyzed two mutants in which the peroxisomal location of the β‐oxidation machinery is in part disturbed. We analyzed Δ pex7 cells that contain virtually normal peroxisomes, except that all matrix proteins that contain a peroxisomal targeting signal type 2 (PTS2, also including thiolase), are mislocalized to the cytosol. In Δ pex5 cells, peroxisomes only contain matrix proteins with a PTS2 in conjunction with all proteins containing a peroxisomal targeting signal type 1 (PTS1, including all β‐oxidation enzymes except thiolase) are mislocalized to the cytosol. We show that intact peroxisomes are an important factor in yeast chronological aging because all pex mutants showed a reduced chronological lifespan. The strongest reduction was observed in Δ pex5 cells. Our data indicate that this is related to the complete inactivation of the peroxisomal β‐oxidation pathway in these cells due to the mislocalization of thiolase. Our studies suggest that during chronological aging, peroxisomal β‐oxidation contributes to energy generation by the oxidation of fatty acids that are released by degradation of storage materials and recycled cellular components during carbon starvation conditions.